Green bioanalytical method development and validation for estimation of Imeglimin hydrochloride using human plasma in pure form by LC–MS/MS - Chandni V. Chandarana; Vidhi H. Vashi; Anjana Bera; Jaiminkumar Patel (Future Journal of Pharmaceutical Sciences, 2025)
Abstract Background A bioanalytical method was developed and validated in accordance with US FDA guidelines for estimating Imeglimin hydrochloride levels in human plasma using liquid chromatography with mass spectrometry (LC–MS/MS). Imeglimin, an oral antidiabetic medication, has demonstrated significant efficacy in reducing high blood sugar levels in individuals with type 2 diabetes, including both Japanese and Caucasian populations. Results The method demonstrated excellent linearity with correlation coefficients (r2) exceeding 0.99 across six calibration curves. Calibration standards showed accuracy within the US FDA’s acceptable range of 99.28–101.09%, and precision varied from 1.10 to 10.19%. Recovery assessment revealed a mean recovery of 76.59% for the internal standard and 85.48% accuracy for the dilution quality control. Stability studies under various conditions, including benchtop, dry extract, wet extract, freeze–thaw, and long term, confirmed the high stability of both the drug and the internal standard, with stability percentages within acceptable limits. The environmental impact assessment utilizing the green analytical procedure index resulted in a score of 0.1, indicating minimal environmental impact, while the analytical greenness metric approach yielded a score of 0.85, indicating efficient resource utilization. Conclusion The validated LC–MS/MS method demonstrates strong linearity, accuracy, and precision, along with high stability under various conditions. Its minimal environmental impact and efficient resource utilization make it suitable for the routine analysis of Imeglimin hydrochloride levels in human plasma. Graphical abstract